Design Rework Prediction in Concurrent Design Environment: Current Trends and Future Research Directions - Arundachawat, Panumas; Roy, Rajkumar; Al-Ashaab, Ahmed; Shehab, Essam (Cranfield University Press, 2009)
This paper aims to present state-of-the-art and formulate future research areas on design rework in concurrent design environment. Related literatures are analysed to extract the key factors which impact design rework. Design rework occurs due to changes from upstream design activities and/or by feedbacks from downstream design activities. Design rework is considered as negative iteration; therefore, value in design activities will be increased if design rework is reduced. Set-based concurrent engineering is proposed as an alternative design approach to mitigate design rework risk, however, duplication effort for designing set of artefacts are still needed to consider before selecting set-based concurrent engineering in design activities.
Organised by: Cranfield University
Keywords: Design Rework; Concurrent Engineering; Literature Review